The Fear of No Future: Guatemalan Migrants, Dispossession and Dislocation - Green, Linda (Anthropologica, 2022)
This article examines the relationship between neoliberal economic policies and practices, state-sponsored violence and international migration through the lived experiences of a Mayan Indian from Guatemala. The Arizona-Mexico border has become "ground-zero" on the war on migrants as tens of thousands cross monthly without legal documents in the hope of creating a future for themselves and their families in the United States. Migration to the U.S. has become one of their last, best options, albeit a dangerous and violent one. This essay explores both the causes and consequences of international migration in the Guatemalan case through the lens of historical political economy to trace how national and international economic policies and practices associated with free trade agreements and peace accords have displaced and dispossessed Guatemala’s indigenous people, and coupled with militarized immigration practices, are in reality an extension of war by other means.